Experiences with BIOFOR reactors at Veas, Norway - Sagberg, Paul; Grundness Berg, Kirsti (Cranfield University, School of Water Sciences, 1996)
Both the local situation in the inner Oslofiord and the political decisions of the countries surrounding the North Sea called for further treatment. Through 1989 and 1990, VEAS put bits and pieces of known technology together to compose a process for nitrogen and phosphorus removal to be installed in the area of the existing sedimentation tanks, only extended in depth. In addition, the process should reduce the amount of sludge considerably. A working hypothesis was presented in 1990 and later named "The VEAS Concept" by prof. H. Odegaard, Techn. Univ. of Trondheim. The status for the development is described in more detail by Sagberg et al. (1995). Figure 1. show the state of the VEAS Concept by end of 1994. Further adjustments has later been made and new will be.Introductory tests were run by VEAS with RBC from Klargester, Mechana and Envirex, with submerged Munthers media, with the Kaldnes moving bed media and with the upflow BIOFOR system from Degremont. After international pre-qualification, call for turn key tenders, which were rejected, and finally licence negotiations, the BIOFOR system was selected for full scale application.